PENGENDALIAN KECEPATAN PUTARAN MOTOR DC PADA PENYANGRAI KOPI MENGGUNAKAN PWM BERBASIS ATMEGA 16 - Azhar, Ade Siti Sarah; Ariyanto, Eko (Vocational School Diponegoro University, 2016)
Ade Siti Sarah Azhar, Eko Ariyanto in this paper explain that Coffee is one of the most popular drinks ever in the history of human civilization. Roasting is one of the most important processes in processing coffee beans that serves to determine the process of forming flavors and aromas in coffee beans. The average roasting process still uses manual methods, so an automatic coffee roaster machine is needed that can support the home roasting process which is equipped with a round control system. It is expected that the roasting process can be carried out quickly. The use of automatic roasting machines aims to save energy and cost and time efficiency. The round control system in this coffee roaster machine uses PWM (Pulse Width Modulation) to regulate speed on a DC motor by regulating the PWM signal which can be done in analog or by using a microcontroller.By using a motor driver, the motor rotation direction can be controlled. When the DC motor rotates its rotation speed can be detected by an optocoupler which then outputs from the optocoupler will send and process data to the Atmega microcontroller 16. The performance of this control system uses a rotation above 60 Rpm with regulated temperatures above 100 ° C. The performance of this control system gets variations in the results of roasting of coffee beans that are close to the standard of coffee, namely at the rotation of 65 Rpm with a temperature of 130 ° C and the roasting time of 18 minutes with the color of Light Roast coffee beans. Keywords :Speed Control, PWM, DC Motor, Driver Motor, Optocoupler, Mikrocontroller Atmega 16.ReferencesBahroin, Anaitul dan Agung Prijo Budijono. 2013. Sistem Kontrol Suhu dan Putaran pada Mesin Penyangrai Kopi Semi Otomatis. Surabaya: Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Surabaya.Ciptadi, W dan Nasution, M.Z. 1998. Pengolahan Biji Kopi. Fakultas Teknologi Institut Pertanian Bogor.Hidayat, Qory. 2012. Pengaturan Kecepatan Motor DC dengan Menggunakan Mikrokontroler Atmega 8535. Balikpapan: Jurusan Teknik Elektronika, Politeknik Negeri Balikpapan.Jumadril, dkk. Pengaturan Kecepatan Motor DC menggunakan PWM Berbasis Mikrokontroler Atmega 16. Batam: Teknik Elektro, Fakultas Teknik, Universitas Batam.Juni S, Eryc Tri, Ponco Siwindarto, dan Eka Maulana. 2015. Penyangrai Biji Kopi Otomatis Untuk Rumah Tinggal. Malang: Jurusan Teknik elektro Universitas Brawijaya.Khamdi, Nur. 2014. Aplikasi Optocoupler dalam Sistem Pengaturan Kecepatan Sepeda Listrik. Riau: Program Studi Mekatronika Jurusan Elektro Politeknik Caltex Riau.Surono, dkk. 2008. Bahasa Indonesia Untuk Perguruan Tinggi. Semarang: Fasindo Press.Yahyfian. 2009. Kendali Putaran Motor DC Menggunakan PWM. Bandung: Jurusan Teknik Elektro, Politeknik Negri Bandung.